Byrsonima crassa Niedenzu (IK): antimicrobial activity and chemical study - M. Sannomiya; D.C. Michelin; C.M. Rodrigues; L.C. Santos; H.R.N. Salgado; C.A. Hiruma-Lima; A.R.S.M. Brito; W. Vilegas (São Paulo State University (UNESP), 2005)
The methanolic extract of leaves from Byrsonima crassa, a Brazilian medicinal plant, was analyzed by CC and HPLC. Four constituents were isolated and identified as quercetin, methyl gallate, (-)-epigallocatechin gallate and quercetin-3-O-(2"-galloyl)-a-L-arabinopyranoside. The methanolic and hydromethanolic extract, as well as fractions, were evaluated regarding their possible antimicrobial activity using in vitro methods. Results showed that both extracts and fractions exhibited significant antimicrobial activity against all tested strains.